Dendritic cell-mediated cross presentation of tumor-derived peptides is biased against plasma membrane proteins. Issue 7 (12th July 2022) - Fessenden, Tim B; Stopfer, Lauren E; Chatterjee, Fiona; Zulueta, Julian; Mesfin, Josh; Cordero Dumit, Therese; Reijers, Irene; Hoefsmit, Esmee P; Blank, Christian; White, Forest; Spranger, Stefani
Abstract : Background: For effective tumor elimination, cytotoxic CD8 + T cells must recognize tumor-derived antigens presented on class I major histocompatibility complex (MHC-I). Despite a general association between the expression of immunogenic antigens, typically neoantigens, and response to immunotherapy, the majority of patients lack strong endogenous responses to most putative neoantigens due to mechanisms that are not well understood. Cytotoxic CD8 + T-cell responses are induced by dendritic cells (DCs) cross-presenting tumor-derived peptides on MHC-I. We hypothesized that cross presentation may form an unappreciated source of bias in the induction of cytotoxic T-cell responses. Methods: We used stable isotope labeling of amino acids combined with immunopeptidomics to distinguish cross-presented from endogenous MHC-I peptides on DCs. To test impacts on T-cell activation, we targeted the model antigen SIINFEKL to specific subcellular compartments in tumor cells, which were used as sources for cross presentation to T cells. In vitro observations were validated using DNA and RNA sequencing data from two cohorts of patients with melanoma undergoing checkpoint blockade therapy. We used a novel quantitative mass spectrometry approach to measure the levels of model antigen on cross-presenting DCs following various means of tumor cell death. Results: DCs exhibited a strong bias for cross-presenting peptides derived from cytoplasmic proteins and against those from plasma membrane proteins, which was confirmed using the model antigen SIINFEKL. In patients with melanoma, the proportion of membrane-derived neoantigens was correlated with reduced survival and failure to respond to therapy. Quantification of cross-presented SIINFEKL revealed that the mode of cell death could overcome DCs' bias against plasma membrane proteins. Conclusions: Cross presentation of cellular antigens by DCs may impose constraints on the range of peptides available to activate CD8 + T cells that have previously gone unappreciated. The share of neoantigens arising from membrane-derived sources may render some tumors less immunogenic due to inefficient cross presentation. These observations carry important implications for the encounter and intracellular processing of cellular antigens by DCs and merit further clinical studies for their therapeutic potential in stratifying patient populations and design of vaccine-based therapies. Sorry this seems to be the only funciton that works yes I confirm TBF, LES and FC are joint first authors. Please that away the line TFB and FC contributed equally. thanks!!